PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN (Studi Pada PT. Inhutani II Kabupaten Kotabaru) - Kaspul Ridani; Khuzaini khuzaini; Rahmi Widyanti (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
The aims of this research were to: 1) describe  education and training program of employees’, 2) describe employees’ job performance, 3) find out the education and training program variable’s could be increasing to employees’ job performance at PT. Inhutani II Kotabaru district.         This research was done by using the explanatory approach which is a research approach to explain the causality or contribution of independent variable toward dependent variable through the argumentation of hypothesis way.         The descriptive result of the research showed that the PT. Inhutani II Kotabaru district still can be categorized in good condition.         While the inferential result of this research showed that education and training are influence toward employees’ job performance at PT. Inhutani II Kotabaru district .         For suggestion, the results of this research are expected not only to give academic contribution for the improvement of human resource, especially as a comprehension toward employees’ behavior in organization, but also to be an input for the users especially for the management section in PT. Inhutani II Kotabaru district , so they can manage the employees’ job behavior for the better performance. Keywords : Education, Training and Job Performance